Exposure factors of Victoria's active motorcycle fleet related to serious injury crash risk. (16th November 2016) - Allen, T.; McClure, R.; Newstead, S. V.; Lenné, M. G.; Hillard, P.; Symmons, M.; Day, L.
ABSTRACT: Objective : The purpose of this study was to describe the nature and extent of current powered 2-wheeler (PTW) risk exposures in order to support future efforts to improve safety for this mode of transport. Methods : A cross-sectional analysis of the control arm of a population-based case-control study was conducted. The control sample was selected from 204 sites on public roads within 150 km of the city of Melbourne that were locations of recent serious injury motorcycle crashes. Traffic observations and measurements at each site were sampled for a mean of 2 h on the same type of day (weekday, Saturday, or Sunday) and within 1 h of the crash time. Photographs of passing riders during this observation period recorded data relating to characteristics of PTWs, age of riders, travel speed of PTWs and all vehicles, time gaps between vehicles, visibility, and protective clothing use. Results : Motorcycles and scooters represented 0.6% of all traffic (compared with 4% of all vehicle registrations). Riders were significantly more likely to have larger time gaps in front and behind when compared to other vehicles. The average travel speed of motorcycles was not significantly different than the traffic, but a significantly greater proportion were exceeding the speed limit when compared to other vehicles (6 vs. 3%, respectively). The age of registered owners of passing motorcycles was 42 years. Over half of riders were wearing dark clothing with no fluorescent or reflective surfaces. One third of motorcyclists had maximum coverage of motorcycle-specific protective clothing. Conclusions : A very low prevalence of motorcyclists combined with relatively higher rates of larger time gaps to other vehicles around motorcycles may help explain their overrepresentation in injury crashes where another vehicle fails to give way. An increased risk of injury in the event of a crash exists for a small but greater proportion of motorcyclists (compared to other vehicle types) who were exceeding the speed limit. An apparent shift toward older age of the active rider population may be reducing injury crash risk relative to exposure time. There is significant scope to improve the physical conspicuity of motorcyclists and the frequency of motorcycle specific protective clothing use. These results can be used to inform policy development and monitor progress of current and future road safety initiatives.